0.75(60x-18)=1.5(8-16x)

Simple and best practice solution for 0.75(60x-18)=1.5(8-16x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.75(60x-18)=1.5(8-16x) equation:



0.75(60x-18)=1.5(8-16x)
We move all terms to the left:
0.75(60x-18)-(1.5(8-16x))=0
We add all the numbers together, and all the variables
0.75(60x-18)-(1.5(-16x+8))=0
We multiply parentheses
45x-(1.5(-16x+8))-13.5=0
We calculate terms in parentheses: -(1.5(-16x+8)), so:
1.5(-16x+8)
We multiply parentheses
-24x+12
Back to the equation:
-(-24x+12)
We get rid of parentheses
45x+24x-12-13.5=0
We add all the numbers together, and all the variables
69x-25.5=0
We move all terms containing x to the left, all other terms to the right
69x=25.5
x=25.5/69
x=17/46

See similar equations:

| Y=0.60x+50 | | 0.75(60x-18=1.5(8-16x | | 3x(x-2)+5=2x | | 2/1/4x=-9 | | 3n2+237n-4590=0 | | 21/4x=9- | | 0.5x+0.75=0.87 | | 3x^2+12x+13=(2x+5)(2x+5) | | 85x+83=91x-283 | | .10x+.25(x+4)=1.7010x+25(x+4)=17010x+25x+100=17035x+100=17035x=70x=2 | | 26z=-910 | | 12x+4=11x15 | | x/5=6=8 | | .10x+.25(x+4)=1.70 | | 9(y+2)=3y+42 | | -5(x+2)+3x=x-2x+2-3x | | -5(x+2)+3x=5x-10 | | -9x=2.7 | | -7/3*8/9=x/27 | | y/5+13=34 | | 32+7=x | | 16n2+n-2304=0 | | 3(4-2x)+2=4(2x+3) | | a/14+6=8 | | 15n2+137n-8740=0 | | 40x=26x+8 | | 36x=x-4x | | (2a-4)+2(a-5)=3(a+1) | | 1-3+a=5/4 | | 3x+9=11x-71 | | -3x^-x+2=0 | | 5.3x-5.14=6.573 |

Equations solver categories